Model of Communicative Writing Instruction through Genre Process Approach and Peer-Review Technique in Undergraduate English Program - Besral Besral (Universitas Negeri Padang, 2014)
The current study looks at possible implementation of Genre Process Approach under Peer-Review technique to improve students’ competence in writing discussion or argumentative essays. As the study focuses on the development of students’ language awareness, teacher’s method and techniques were explored to investigate: (a) The extend to which students’ understanding of language and rethorics get improved; (b) Ways in which students appreciate English and its culture; and (c) Students’ ability to use English in terms of structure and vocabulary as reflected in their academic writing. Data were collected through interview with some students soon after the process of Peer-Review, while the assessment of students’ writing products were done by two independent raters using Jacob’s (1981) criteria. It was found that students’ improvement in understanding of language and rethorics include pluralization, capitalization, present verb ‘have’, future tense, and use of past form of modal (should and must). Students appreciated English since it promises good job in the future. Students perceived English as an interesting language that the users seem to be honest. Peers and discussion with the lecturer gave significant impact to their oral skill, however, such activities presented a little impact to the betterment of their writing products. The findings suggest that language awareness in the teaching and learning process of Essay Writing does not only include linguistic aspects, but also rethorical styles, attitudinal education, and metacognitive opportunties as well. To achieve the ultimate goals of ELT, therefore, peer-review activities needs to be collaboarated with other related disciplines.